2017
DOI: 10.4103/ijccm.ijccm_250_17
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of mortality in Intensive Care Unit of a Level III military hospital of Bangladesh

Abstract: Background:Mortalities in Intensive Care Units (ICUs) are high and widely variable. The unpredictability of death rates is attributable to age, sex, nature and severity of illness, comorbidity, well-timed medical attention, quality of the attending staffs, iatrogenic events, total management facilities, and overall grade of the ICU in general.Materials and Methods:A total of seventy patients who died in the ICU of a Level III Combined Military Hospital within a period of 2 years were studied in retrospect to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This holds true for both adult and pediatric intensive care units. 22,23 Longer duration of stay has been linked with various problems among the patients admitted in the ICU in the past. Poor outcome i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This holds true for both adult and pediatric intensive care units. 22,23 Longer duration of stay has been linked with various problems among the patients admitted in the ICU in the past. Poor outcome i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The mean Intensive Care Unit (ICU) mortality rate reported in the United States ranged from 8 to 19% or about 500,000 deaths per year [23]. Alam conducted a study in Bangladesh and showed that the number of ICU beds accounted for 1.8% of the total hospital beds; however the death rate in the ICU was 3.58% of hospital deaths [24]. According to Siddiqui, there were 1134 deaths in three ICU wards in Singapore from July 2010 to March 2015, accounting for 7% of all hospital deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing conditions were coded as 1 (present) or 0 (absent). Age was demarcated at 65 years, with those aged >65 years coded 1 and those aged ≤65 years coded 0 [36][37][38][39]. For the sex variable, men were assigned 1 and women were assigned 0 [40].…”
Section: Featuresmentioning
confidence: 99%